The THE EFFECT OF PAD, CAPITAL EXPENDITURE, SILPA AND BUDGET CHANGES ON REGIONAL ECONOMIC GROWTH DURING THE PANDEMIC IN CENTRAL JAVA - Kartika Widyasari (Politeknik Bisnis Indonesia, 2022)
Due to the covid-19 pandemic, which is assumed to be equivalent to the economic crisis, regions in Central Java are one of the regions that are economically highly affected. This is evidenced by the decrease in GRDP to -2.65 in the mid-May 2021 period. The purpose of this study was to determine the effect of PAD, capital expenditure, SILPA and budget changes on regional economic growth in regencies and cities in Central Java. The research methods used are quantitative methods and use descriptive statistical test techniques, classical assumption tests, multiple linear regresi analysis, model fish test and hypothesis testing as a data analysis technique. The results showed that PAD, capital expenditures and SILPA had a positive effect on economic growth. Meanwhile, budget changes have no effect on economic growth.